Expression of the glycolytic enzymes enolase and lactate dehydrogenase during the early phase of Toxoplasma differentiation is regulated by an intron retention mechanism. Issue 6 (11th April 2015) - Lunghi, Matteo; Galizi, Roberto; Magini, Alessandro; Carruthers, Vern B.; Di Cristina, Manlio
Summary The intracellular parasite Toxoplasma gondii converts from a rapidly replicating tachyzoite form during acute infection to a quiescent encysted bradyzoite stage that persists inside long‐lived cells during chronic infection. Bradyzoites adopt reduced metabolism and slow replication while waiting for an opportunity to recrudesce the infection within the host. Interconversion between these two developmental stages is characterized by expression of glycolytic isoenzymes that play key roles in parasite metabolism. The parasite genome encodes two isoforms of lactate dehydrogenase (LDH1 and LDH2) and enolase (ENO1 and ENO2) that are expressed in a stage‐specific manner. Expression of different isoforms of these enzymes allows T. gondii to rapidly adapt to diverse metabolic requirements necessary for either a rapid replication of the tachyzoite stage or a quiescent lifestyle typical of the bradyzoites. Herein we identified unspliced forms of LDH and ENO transcripts produced during transition between these two parasite stages suggestive of an intron retention mechanism to promptly exchange glycolytic isoforms for rapid adaptation to environmental changes. We also identified key regulatory elements in the ENO transcription units, revealing cooperation between the ENO2 5′‐untranslated region and the ENO2 intron, along with identifying a role for the ENO1 3′‐untranslated region in stage‐specific expression.